PENGARUH PROFITABILITAS, ASSET TANGIBILITY, FIRM SIZE, DAN GROWTH OPPORTUNITY TERHADAP FINANCIAL LEVERAGE - Melisa Melisa; Herlin Tundjung; Djeni Indrajati (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research aims at how the effect of profitability, asset tangibility, firm size, and growth opportunity towards financial leverage on manufactur industry listed on the Indonesia Stock Exchange during 2017-2019. Sample was selected using purposive sampling method and the valid data was 35 companies. Data processing techniques using multiple regression analysis what helped by Eviews program (Econometric Views) for Windows released 11 and Microsoft Excel 2016. The results of this study indicate that profitability has a significant and negative influence on financial leverage while tangibility, firm size, and growth have insignificant and positive influence on financial leverage. The implication of this study is the need to increase the role of management to manage the financial leverage that will bring a good signal for investors.